Mejoramiento en los comportamientos de autocuidado después de una intervención educativa de enfermería con pacientes con falla cardíaca (2012)
ABSTRACT: To evaluate the improvement in self-care behaviors after a nursing educational intervention in patients with heart failure. Methodology. The study had the participation of 29 patients over 30 years of age, who attended in 2010 the cardiovascular healthcare program of a hospital institution in Medellín (Colombia) and who signed the informed consent and received for nine months a nursing educational intervention consisting of group educational meetings, telenursing sessions, home visits, and support leaflet. The study applied Artinian’s Self-care scale validated in the field, composed of 28 items distributed in four dimensions (request for help, adaptation to disease, and adherence to pharmacological and non-pharmacological treatments). To evaluate changes in these behaviors, the scale was applied at the beginning and end of the study. Results. Bearing in mind that the maximum possible score in the scale is 84, the patients had initial and final median scores of 40 and 53 (p < 0.05). The dimensions in which the most positive changes were observed were: request for help, adaptation to the disease, and adherence to the pharmacological treatment; regarding adherence to the non-pharmacological treatment, two behaviors did not obtain favorable changes (reduction in salt intake and measurement of the amount of urine eliminated). Conclusion. The nursing educational intervention conducted in our study had beneficial effects on most of the self-care behaviors assessed in individuals with HF.